The investigation of integration between platforms using LDAP / Izwan Razif Mohd Johar - Mohd Johar, Izwan Razif (2005)
In Malaysia, LDAP still in the early phase and not widely implemented. The Lightweight Directory Access Protocol, better known as LDAP, is based on the X.500 standard, but significantly simpler and more readily adapted to meet custom needs. This research is about the implementation of LDAP in Malaysian environment. Since LDAP is multiplatform, so this research focuses on the integration platform and investigates the structure of LDAP that used in Malaysian company. This research also focuses on how far LDAP is implemented in an organization. In Malaysia, LDAP commonly used in web mail directory, single sign on, authentication directory and personal information directory. Survey has been done on users of LDAP technology to identify implementation and usage of LDAP in their companies. It was found that most of companies in Malaysia use LDAP protocol in address book directory and most of them have good impression on LDAP usage. LDAP make information easy to manage and more stabilize and secure. Interview session with the management found that LDAP usage is still in early stage of deployment and still having difficulties in maintaining the LDAP structure and insufiBcient knowledge among the technical person e.g. system administrator, system analyst etc. IV